Dampak Polusi Plastik Bahari terhadap Sosial Ekonomi Pariwisata Bekerlanjutan pada Pesisir Pantai Kendari dan Konawe - Imran, Muhammad (Program Studi Perbankan Syariah, IAIN Palopo, 2024)
Marine plastic waste has become a big scourge for local governments in Indonesia in developing the coastal tourism ecosystem. To reduce marine plastic waste, local governments in Indonesia have implemented various policies, but the impact has not been published well academically. This study aims to provide an in-depth approach to the consequences of marine plastic waste on socio-economic growth, especially on the coastal tourism industry in Kendari Southeast Sulawesi, such as how local communities and tourism visitors receive the consequences of the prohibition of littering, as well as the potential for behavior and change. In addition to conducting a survey of changes in the behavior of leaders and managers in beach tourism, this study will also conduct a statistical approach to measure and test the impact of economic growth of Kendari city as the capital of Southeast Sulawesi Province due to marine plastic waste. The results of the multiple linear regression model estimate show that marine plastic waste has a negative effect on the GDP of Kendari city per capita (coefficient -0.10, p-value 0.000). This means that an increase in the amount of marine plastic waste per kilometer of beach in the city of Kendari will reduce the GDP of the city of Kendari per capita. In addition, the number of tourist visits per year in the city of Kendari has a positive effect on the GDP of Kendari city per capita (coefficient 0.01, p-value 0.019). This shows that the increase in the number of tourist visits per year in the city of Kendari will increase the GDP of the city of Kendari per capita. The results of this study show that marine plastic waste has a negative effect on the socio-economy of local communities and beach tourism visitors in Kendari and Konawe.